Modified thermal resistance networks model for transverse thermal conductivity of unidirectional fiber composite. (December 2017) - Jiang, Haiqing; Yi, Zhibing; Cheng, Pan; Kong, Chuncai; Li, Mufang; Wang, Xiaojun; Liu, Ke; Takagi, Hitoshi; Wang, Dong; Yang, Zhimao
Abstract: In this paper, a facile method based on thermal-electrical analogy technique was developed to solve the heat flow transfer behavior in unidirectional fiber reinforced polymer composite. A modulating thermal resistance R md, correcting the heat flux, was introduced in the thermal resistance network to analyze two-dimensional square arrayed square fiber model of composite for its effective transverse thermal conductivity. The result of present method showed a better agreement with that of finite element method (FEM) than existed parallel or series thermal resistance network. Around this consideration, the composite reinforced by fiber with circular-cross section was also modeled to evaluate the transverse thermal conductivity, which still exhibit well consistent with experimental data. It indicates that the proposed method is enough accurate and effective for evaluating the thermal conductivity of unidirectional fiber composite and provides a facile approach to understand the complicated heat flow transfer behavior in composites. Highlights: Thermal-electrical analogy technique has been used to analyze heat transfer behavior. Modulating thermal resistance Rmd has been introduced to thermal resistance network. Result of present method showed good agreement with that of finite element method. Heat flow in unidirectional circular fiber composite has also been solved by present method. Predicted K of unidirectional fiber composite is highly consistent with experimental results.